Washington 'Steps' Up: A 10-Step Quality Improvement Initiative to Optimize Breastfeeding Support in Community Health Centers. (November 2015) - Schwartz, Rachel; Ellings, Amy; Baisden, Amy; Goldhammer, Camie Jae; Lamson, Erica; Johnson, Donna
Background: Breastfeeding initiation in Washington State (Northwest United States) is high, yet rates plummet by 3 months postpartum. In the United States, national quality improvement (QI) efforts to improve breastfeeding outcomes have largely focused on hospital maternity care practices through implementation of the Ten Steps to Successful Breastfeeding . This framework has not extended similarly to primary care clinics, a key site for supporting continued breastfeeding following hospital discharge. This article details a pilot effort with community clinics to implement 10 evidence-based steps to support breastfeeding in the clinic setting and to evaluate the process and outcomes. Objective: A public-private-academic partnership developed and piloted a 10-step clinic breastfeeding support strategy and focused resources, training, and technical assistance on primary care clinics to help facilitate best-practice policy and environmental changes to improve clinic breastfeeding support. Methods: Eight health centers, serving predominantly Latino and Native American communities, worked to systematically implement 10 evidence-based steps developed for the community primary care setting. An evidence table, self-assessment with scoring criteria, tool kit, and provider reference documents were developed to guide clinics. Results: At baseline, clinics had 2 steps, on average, already in practice (range, 1-4 steps); by final assessment, an average of 7 steps was implemented (range, 5-9 steps). Within 6 months from pre-intervention to post, clinics fully operationalized between 2 and 7 steps. Conclusion: Catalyzing clinic QI efforts through an evidence-based 10-step model is an effective way to optimize primary care breastfeeding support and to strengthen the continuum of care for breastfeeding mothers and babies following hospital discharge.